Regulatory Reconstruction of the Application of Digital Evidence in Realizing Children's Rights (Study of the Directory of Decisions of the Supreme Court of the Republic of Indonesia) - Libra, Robert; Okfalisa, Okfalisa; Aslati, Aslati (Faculty of Law, Universitas Pekalongan, 2024)
The development of technology continues and develops in accordance with the times. The use of technology is also carried out to the context of daily life so that life becomes more practical. Then, this context is also very close to the use of technology in the judicial process through the e-court system. This is what makes Constitutional Court Decision Number 46/PUU-VIII/2010 concerning the Examination of Article 43 paragraph (1) of Law Number 1 Year 1974 concerning Marriage appear and change the paradigm of proof from the determination of children outside marriage can be done by using technology in the form of DNA tests. In this case, electronic evidence or digital evidence can be strong evidence to recognize the father's nasab position over the child. The research method used in this research is Normative Juridical with a statutory approach and a case approach. The results and discussion of this study found that it turns out that the application of digital evidence can realize children's rights when looking at several existing decisions. Of the 10 (ten) decisions and/or court decisions that have been reviewed, all of them use digitized evidence and make the judge's view more objective, resulting in a decision that recognizes the father's lineage to the child. The context of this recognition is the essence that the concept of child recognition makes his rights fulfilled and the father cannot deny that the child is his own child. In addition, DNA evidence, CCTV and photos and videos exist to strengthen the position of the father's lineage to a child whose father previously did not recognize his own child. Regulatory reconstruction in the application of digital evidence to realize children's rights is carried out by changing the provisions of the Religious Courts Law and the Marriage Law in terms of strengthening the position of children's rights.